Normal stress components during shear tests of metal sheets. (December 2019) - Pereira, A.F.G.; Prates, P.A.; Oliveira, M.C.; Fernandes, J.V.
Highlights: For a strong anisotropy, the normal stresses components should not be neglected. The specimen geometry and boundary conditions influence the normal stresses. The rotation of the material axes, affects the stresses evolutions. The analytically predicted normal stresses agree with those numerically evaluated. Abstract: The normal stress components that arise during the shear test of metal sheets are numerically investigated. Simulations of the shear test are used to study the influence of the material anisotropy, specimen geometry, boundary conditions and loading direction on those components. For anisotropic materials, the normal stresses can reach magnitudes similar to those of the shear component. These components arise due to the imposed boundary conditions and the stress disturbance at the free ends of the specimen and its evolution is affected by the rotation of the material axes. An analytical approach to estimate these components is proposed. The predicted normal components agree with those evaluated numerically and their use allows the correct determination of the equivalent stress vs . strain curve.